Bio‐Inspired Cryo‐Ink Preserves Red Blood Cell Phenotype and Function During Nanoliter Vitrification. (22nd July 2014) - El Assal, Rami; Guven, Sinan; Gurkan, Umut Atakan; Gozen, Irep; Shafiee, Hadi; Dalbeyler, Sedef; Abdalla, Noor; Thomas, Gawain; Fuld, Wendy; Illigens, Ben M. W.; Estanislau, Jessica; Khoory, Joseph; et al.
<x xml:space="preserve">Abstract</x> Current red‐blood‐cell cryopreservation methods utilize bulk volumes, causing cryo‐injury of cells, which results in irreversible disruption of cell morphology, mechanics, and function. An innovative approach to preserve human red‐blood‐cell morphology, mechanics, and function following vitrification in nanoliter volumes is developed using a novel cryo‐ink integrated with a bioprinting approach. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>